Potato - Earle, Rebecca (Object lessons., 2019)
Baked potatoes, Bombay potatoes, pommes frites ... everyone eats potatoes, but what do they mean? To the United Nations they mean global food security (potatoes are the world's fourth most important food crop). To 18th-century philosophers they promised happiness. Nutritionists warn that too many increase your risk of hypertension. For the poet Seamus Heaney they conjured up both his mother and the 19th-century Irish famine.